Optimization of an organic Rankine cycle as bottoming cycle of a 1 kWe GENSET for residential applications. (September 2017) - Lavernia, Alejandro; Ziviani, Davide; Shaffer, Bryce; Bansal, Kunal; Groll, Eckhard A.
Abstract: A novel 1 kWe GENSET featuring an internal combustion engine (ICE) operating on Spark-Assisted Compression Ignition (SACI) combustion of natural gas is under development to achieve an overall power generation efficiency of 40%. The aim is to create an efficient electricity generation system that can provide the energy necessary for light residential use at high thermal efficiency and low user cost. In order to achieve such power generation efficiency for a small-scale energy/heat production unit, an organic Rankine cycle (ORC) has been proposed as a bottoming cycle to recover heat from the exhaust of the small internal combustion engine. The ORC has been optimized to operate with a heat source inlet temperature of 400 ºC, which is necessary for use with the integrated catalytic converter evaporator proposed for the system. By means of a thermodynamic cycle model, the final cycle architecture has been identified along with the design of a novel two-stage scroll expander integrated with working fluid pump. Results showed that by employing R1233zd(E) as the working fluid, the theoretical ORC thermal efficiency is as high as 14.79% with a net ORC power output of 148.6 W.